Big Data and Agricultural Supply Chains: Opportunities for Increased Food Security - Dimitrios Tsiolias; Christos Keramydas; Eleftherios Iakovou; Dimitrios Vlachos (Operational Excellence in Logistics and Supply Chains: Optimization Methods, Data-driven Approaches and Security Insights. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 22, 2015)
Today's interconnected digital world with its multitude of data-collecting devices and means along with augmented data processing capabilities has unlocked new possibilities for increasing the efficiency of contemporary agricultural supply chains, including production, processing and distribution operations. Furthermore, issues such as climate change, global population increase, the rise of alternative energy sources, agricultural technological advances, and shifting consumer dietary preferences have been reshaping the global contemporary food management landscape. These factors, in conjunction with the limited availability of arable land, present challenges regarding the availability, accessibility, utilization, and stability of food worldwide. We present an up-to-date critical synthesis of the most acute challenges of food security and provide a first effort at identifying ways in which big data could help alleviate them. Specifically, satellite imagery and data, groundwater monitoring, the Internet-of-Things (IoT), viewing advantages through the use of drones, updated global atlases, as well as regional and crop yield mapping, precision agriculture, demand prediction accuracy, and the ease-of-use of terminals such as smartphones and tablets are some of the tools of the information age that demonstrate great potential towards increasing the efficiency and competitiveness of food chains worldwide and, ultimately, ensuring food security.
10419/209191; https://econpapers.repec.org/RePEc:zbw:hiclpr:22
Keywords: 650; Big Data; Food Security; Agricultural Supply Chains; Sustainability